The role of two-component regulatory systems in environmental sensing and virulence in Salmonella. (4th July 2021) - de Pina, Lucindo Cardoso; da Silva, Fernanda Stephens Hermes; Galvão, Teca Calcagno; Pauer, Heidi; Ferreira, Rosana Barreto Rocha; Antunes, L. Caetano M.
Abstract: Adaptation to environments with constant fluctuations imposes challenges that are only overcome with sophisticated strategies that allow bacteria to perceive environmental conditions and develop an appropriate response. The gastrointestinal environment is a complex ecosystem that is home to trillions of microorganisms. Termed microbiota, this microbial ensemble plays important roles in host health and provides colonization resistance against pathogens, although pathogens have evolved strategies to circumvent this barrier. Among the strategies used by bacteria to monitor their environment, one of the most important are the sensing and signalling machineries of two-component systems (TCSs), which play relevant roles in the behaviour of all bacteria. Salmonella enterica is no exception, and here we present our current understanding of how this important human pathogen uses TCSs as an integral part of its lifestyle. We describe important aspects of these systems, such as the stimuli and responses involved, the processes regulated, and their roles in virulence. We also dissect the genomic organization of histidine kinases and response regulators, as well as the input and output domains for each TCS. Lastly, we explore how these systems may be promising targets for the development of antivirulence therapeutics to combat antibiotic-resistant infections.